The distribution of science communication teaching around the globe - Roche, Joseph (My University, 2023)
In the context of a special issue of this journal focused on teaching science communication, we present a map of the geographical distribution of 122 science communication teaching programmes from 31 countries around the world. This mapping study resulted from a collaboration between members of the PCST Teaching Forum and the research team at GlobalSCAPE, a research project funded by the European Commission to explore the global state of science communication. Our findings highlight the concentration of these programmes in the U.S.A. and Europe, and the dominance of English as the language of instruction. We ponder the causes and implications of the disparities in opportunities for studying science communication in other world regions and languages. The dearth of science communication educational pathways in developing countries may limit the professionalisation of the field, as well as research and evidence-based practice that is locally needed and relevant.
PUBLISHED
Keywords: Professionalism, professional development and teaching in science communication; Science communication degree programmes; Science communication teaching; Higher Education; SCIENCE COMMUNICATION